Study Habits, Mathematics Performance And Gender Differences Of Agriculture Students Amidst The New Normal - Travero, Arnel; Nagal, Cyril John; Herda, Rozanah Katrina (Wahana Pendidikan, 2025)
The paradigm shift caused by the pandemic led the students to adjust their study habits as opposed to what was conventional during face-to-face learning. This study presented the study habits, mathematics performance, and gender differences of Agriculture students during the new normal. The researchers surveyed 193 Agriculture students, enrolled in the first semester of SY 2021-2022, using an adapted questionnaire to assess students’ study habits, and the final examination test to quantify students’ mathematics performance. Mean, standard deviation, correlation analysis, and t-test for independent means were utilized in treating the data. Results showed a moderate positive relationship between students’ study habits and their mathematics performance. With regards to student’s study habits, no significant difference was found between the two sexes; however, female students were found to have significantly performed better in mathematics compared to male students. From these findings, the researchers recommend that students should be encouraged to adopt good study habits as this relates to their performance. Further, instructors should devise strategies that would cater mathematics performance of both sexes.